Bah Bolon River 1980-2023: The History of Pollution and River Used - Abiyulail Alatas Abus; Meilisna Purba; Tasnim Lubis (Tradition and Modernity of Humanity, 2024)
The existence of the Bah Bolon River is related to the surrounding community. This study was diachronic research on the history and dynamics of the Bah Bolon River from 1980-2023. Bah Bolon River is related to environmental, social and economic changes in terms of river pollution. This study aimed to invent information on the condition of the Bah Bolon River in Pematang Siantar City, North Sumatra in 1980-2023 with a focus on pollution of the Bah Bolon River and its use for the surrounding community. The method used was a historical method which consists of four stages, namely heuristics, criticism, interpretation, and historiography. Data collection was carried out through a literature review and in-depth interviews. Literature data was taken from official documents and articles regarding the Bah Bolon River from 1980-2023. In-depth interviews were conducted with informants who met the criteria of (1) full enculturation; (2) direct involvement; (3) unfamiliar cultural atmosphere; (4) sufficient time; and (5) non-analytic. The chronological analysis carried out includes the transformation of river flows, the use of water resources, and their impact on the lives of local communities. The results showed that there were changes in land use, social structure, and community economy over time. These findings contribute to a deep understanding of the dynamics of the Bah Bolon River in the 1980s, creating a foundation for evaluating the impact of environmental change on human life. The results of this research contribute to the understanding of environmental history, social change, and community adaptation to ecological change. The implications of this research can be used as a basis for future environmental conservation and water resource management policies while exploring the historical and heritage value of the Bah Bolon River.